What teachers need for a sound assessment - Pastore, Serafina (Form@re - Open Journal per la formazione in rete, 2017)
School reforms, currently underway, are focusing on what is taught, how it is learned, and how it is assessed in innovative ways that foster students’ learning. Educational policy and research trends, both at the national and international level, confirm the need that teachers acquire and develop assessment competencies in order to guarantee an evaluation school-system quality and to monitor and foster students’ learning. Several research studies have demonstrated how teachers tend to not use assessment information (especially large-scale assessment data) for their decision-making within the classroom. The present article lays out the teacher assessment literacy debate focusing on the evolution of this concept. After a critical review of the main studies on teacher assessment literacy, it describes the first results of an explorative research. Cosa serve agli insegnanti per ben valutare Nell’ambito delle attuali riforme in campo scolastico, una rinnovata attenzione è stata posta sugli aspetti di ciò che si insegna, di ciò che si apprende e di come lo si valuta in modo innovativo al fine di promuovere l’apprendimento degli studenti. Gli orientamenti politici e gli indirizzi di ricerca più recenti, a livello nazionale e internazionale, ribadiscono la necessità per gli insegnanti di acquisire e sviluppare competenze tali da garantire un sistema di valutazione di qualità e, al contempo il monitoraggio e la promozione dell’apprendimento. In realtà, diverse ricerche al riguardo hanno già dimostrato come gli insegnanti tendano a non usare i dati e le informazioni acquisite attraverso la valutazione (specie se su larga scala) per il loro decision-making all’interno della classe. Il presente articolo si colloca nell’ambito delle indagini sulla teacher assessment literacy. Nel riportare l’evoluzione di questo concetto prova a individuarne le principali componenti affiancando all’analisi della letteratura gli esiti di un’indagine esplorativa sul campo.